DIMENSIONS OF YOUNG ADULT LITERATURE: THE READING ON FIVE FEET APART - Noviani, Syafika Salsa; Cahyaning Rahayu, Anik (Annual International Conferences on Language, Literature, and Media, 2022)
This study aims to describe the characteristics of Young Adult Literature genre found in the novel. Young Adult Literature’s characteristics relate to the novel’s intrinsic elements which consists of character, theme, plot, and point of view. The approach used in analysing the novel is structuralism approach. This research uses descriptive qualitative method. The result of the analysis states that Five Feet Apart is categorized into young adult literature since it conforms the genre’s characteristics. The characters of the novel have a physical appearance and the way they behave as well as interact with each other. Moreover, the characters in the novel have a change in attitude and way of thinking. Seen from the analysis, the plot is going fast and the storyline is written in the present. Theme in the novel is about romance because the novel tells the love story of the two young adult people who suffer from lungs illness, named Stella and Will. There are two points of view from young adult protagonists as the main characters in the novel. The point of view changes in every chapter because the story is sometimes told by Stella and sometimes by Will. Finally, it can be concluded that characteristics of Young Adult Literature genre are found in the novel Five Feet Apart.